Development of Post-Distance Education School Adjustment Scale: Validity and Reliability Study - Emre Musa Turhan (European Scientific Journal, ESJ, 2023)
In this study, it was aimed to develop a scale to measure the school adjustment levels of university students after distance education. 35 draft items were prepared in line with the literature review and expert opinions. After the opinions of the field experts, necessary corrections were made in the draft scale form and a 32-item scale was reached. The data were collected from 437 university students. As a result of the Exploratory Factor Analysis (EFA), a three-dimensional structure consisting of 21 items and three dimensions as “Social Adjustment”, “Adjustment with Faculty Members and Students” and “Affective Adjustment” and explaining 50.45% of the variance was reached. Fit indices calculated by confirmatory factor analysis (CFA) were obtained as χ²/Df=3.29, RMSEA= 0.073, CFI= 0.92, GFI= 0.91, AGFI= 0.88. These observed values show that the model has an acceptable goodness of fit. When the items with low factor scores and items in other dimensions were examined, it was seen that the model fit indices were at the desired level after 5 items were excluded from the scale. The alpha reliability of the whole scale was determined as 0.89. Alpha reliability for each component was calculated as 0.88, 0.82 and 0.79, respectively. The results show that Post-Distance Education School Adjustment Scale is a valid and reliable measurement tool that can measure university students’ adjustment to school after distance education.